An Implementation Framework Overview of Non-Intrusive Load Monitoring - Omar Al-Khadher; Azharudin Mukhtaruddin; Fakroul Ridzuan Hashim; Hussin Mamat; Muhammad Mokhzaini Azizan (SDEWES Centre, 2024)
Indexed by WOS/Scopus/ERA